2007
DOI: 10.1007/s11581-007-0169-9
|View full text |Cite
|
Sign up to set email alerts
|

Defect thermodynamic and transport properties of nanocrystalline Gd-doped ceria

Abstract: Nanocrystalline CeO 2 -doped (5, 7.5, 10, and 15 mol%) Gd 2 O 3 powders, with a particle size of about 17 nm, were synthesized through the combustion of glycine/ nitrate gels. Dense nanocrystalline materials were obtained by hot uniaxial sintering. Optical microscopy, scanning electron microscopy and transmission electron microscopy examinations, as well as X-ray diffraction analyses, have allowed us to characterize these polycrystals. The grain sizes, included between ∼10 and 80 nm, depend on both the sinteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…As indicated in Table I, the early work of Chiang 8 agrees with the expectation that, in contrast to undoped ceria, nanostructuring in the presence of trivalent dopants decreases overall conductivity; even for grain sizes of only 10 nm, distinct bulk and grain boundary responses were detected in the impedance spectra with grain boundaries adding to the overall material resistance. The result is supported by more recent work from Jasinski, 13 Surble et al, 14 Perez-Coll et al, 15 and Ruiz-Trejo et al 16 While the later studies have been directed toward the exploration of H 2 O uptake and proton transport along grain boundaries, the data nevertheless reveal that doped ceria with grain size of ∼100 nm has resistive grain boundaries. The works of Bellino et al 17 and of Anselmi-Tamburini et al 18 stand in stark contrast to these studies.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…As indicated in Table I, the early work of Chiang 8 agrees with the expectation that, in contrast to undoped ceria, nanostructuring in the presence of trivalent dopants decreases overall conductivity; even for grain sizes of only 10 nm, distinct bulk and grain boundary responses were detected in the impedance spectra with grain boundaries adding to the overall material resistance. The result is supported by more recent work from Jasinski, 13 Surble et al, 14 Perez-Coll et al, 15 and Ruiz-Trejo et al 16 While the later studies have been directed toward the exploration of H 2 O uptake and proton transport along grain boundaries, the data nevertheless reveal that doped ceria with grain size of ∼100 nm has resistive grain boundaries. The works of Bellino et al 17 and of Anselmi-Tamburini et al 18 stand in stark contrast to these studies.…”
supporting
confidence: 52%
“…The result is supported by more recent work from Jasinski, 13 Surble et al, 14 PerezColl et al, 15 and Ruiz-Trejo et al 16 While the later studies have been directed toward the exploration of H 2 O uptake and proton transport along grain boundaries, the data nevertheless reveal that doped ceria with grain size of ∼100 nm has resistive grain boundaries. The works of Bellino et al 17 and of Anselmi-Tamburini et al 18 stand in stark contrast to these studies.…”
supporting
confidence: 52%
“…22 There are several synthesis methods, including conventional ceramic (solid-state) and soft-chemical methods such as glycine-nitrate, 27 coprecipitation, 28 and polymerization, 29 that are employed to prepare doped ceria electrolytes. These preparation methods play a significant role in determining the microstructure and particle size distributions, which influence the electrical conductivity, [30][31][32][33] and particlesize-dependent conductivity was explained using the space charge model. 34,35 Recently, we have re-examined the chemical stability of Y-doped BaCeO 3 in CO 2 at a temperature range of 600-1000 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is also important to mention here that the electrical conductivity of materials significantly changes with crystalline sizes. For example, Surble et al [52] showed that the ionic conductivity of Gd-doped CeO 2 increases as the grain size decreases and the ionic conductivity goes through a maximum at about 300-500 nm. In a recent work, Tschope and co-worker showed that about two orders of magnitude lower electrical conductivity compared to microcrystalline material was observed [53].…”
Section: Resultsmentioning
confidence: 99%